Human Blood Lipoprotein Predictions from 1H NMR Spectra: Protocol, Model Performances, and Cage of Covariance - Khakimov, Bekzod; Hoefsloot, Huub C. J.; Mobaraki, Nabiollah; Aru, Violetta; Kristensen, Mette; Lind, Mads V.; Holm, Lars; Castro-Mejía, Josué L.; Nielsen, Dennis S.; Jacobs, Doris M.; Smilde, Age K.; Engelsen, Søren Balling (Analytical chemistry (Washington), 2022)
Lipoprotein subfractions are biomarkers for the early diagnosis of cardiovascular diseases. The reference method, ultracentrifugation, for measuring lipoproteins is time-consuming, and there is a need to develop a rapid method for cohort screenings. This study presents partial least-squares regression models developed using 1H nuclear magnetic resonance (NMR) spectra and concentrations of lipoproteins as measured by ultracentrifugation on 316 healthy Danes. This study explores, for the first time, different regions of the 1H NMR spectrum representing signals of molecules in lipoprotein particles and different lipid species to develop parsimonious, reliable, and optimal prediction models. A total of 65 lipoprotein main and subfractions were predictable with high accuracy, Q 2 of >0.6, using an optimal spectral region (1.4–0.6 ppm) containing methylene and methyl signals from lipids. The models were subsequently tested on an independent cohort of 290 healthy Swedes with predicted and reference values matching by up to 85–95%. In addition, an open software tool was developed to predict lipoproteins concentrations in human blood from standardized 1H NMR spectral recordings.